RANCANG BANGUN SISTEM KONTROL DAN MONITORING LAMPU OTOMATIS MENGGUNAKAN ARDUINO DENGAN METODE FUZZY LOGIC BERBASIS ANDROID (Studi Kasus Koridor Lantai 1 dan 2 Fakultas Ilmu Komputer) - Rahmat Ramdoni; Sugeng Supriyadi; Nunu Nugraha (NUANSA INFORMATIKA, 2018)
The rapid development of technology in various field, including the field of electronic, necessity of facility and comfort in controlling the electric devices are important, especially in controlling and monitoring the lamps. Nowdays society can control the electrical devices only with the switch connected by cabel. Then, it is needed a control system and monitoring lamps automatically. One of the systems is using micro controller. Based on the problems identified in Computer Sciences Faculty, system for controlling and monitoring lamps hasn’t  run efectivelly because it still uses manual and it has not got the lamps should be burn. Method of software development used in this research is Rational Unified Process (RUP) method by using design of Unified Modeling Language (UML) such as using case diagram, scenario, activity diagram, class diagram dan sequence diagram. Meanwhile, the problem solving method is using Fuzzy Logic method. System of controlling and monitoring the lamps built by fuzzy logic method is efective automaticallty. The system can be applied to the research object and assist in the process of controlling and monitoring the lamp automatically.Keyword : Rational Unified Proces method, Arduino, Unified Modeling Language,Fuzzy Logic, Controlling and Monitoring the Lamps